Social Workers in Animal Shelters: A Strategy Toward Reducing Occupational Stress Among Animal Shelter Workers - Hoy-Gerlach, Janet; Ojha, Mamta; Arkow, Phil (Frontiers in Veterinary Science, 2021)
Animal shelter workers (ASWs) are at disproportionate risk of moral injury, secondary trauma, compassion fatigue, and burn-out. While there is an emerging body of literature developing on understanding the nuances of these experiences for ASWs, little work has been done on developing strategies to ameliorate occupational stressors and the negative effects of such for ASWs. Within this paper, occupational risks and protective factors for ASWs are summarized, and the emergence of social work within animal shelter settings as one strategy for helping to ameliorate the occupational stress experienced by ASWs is delineated.